Theory and Method in Urban Ethnomusicology - Jurková, Zuzana (Lidé města, 2012)
Most of us live in cities. Surrounded by an urban environment, more and more ethnomusicologists are investigating urban phenomena. Despite that, when we started with more systematic research of Prague musics, we couldn’t find a theory in which “urbanness” would be conceived as a substantial feature.